PEMANFAATAN ARDUINO NANO V5 DALAM MERANCANG PROGRAMABLE LOGIC CONTROL - Utami, Suci Sri; Sukamto, Anton; Cahyadi, Septian (Jurnal Informatika Kesatuan, 2022)
Programmable Logic Control or PLC is the control of a microprocessor for industry, especially in the field of automation, which functions as an alternative to mechanical relays used in controlling complex or complex processes. Programmable Logic Control, in general, has a relatively high price, and not everyone can learn it. For this reason, Arduino nano is used for Programable Logic Control V5. Selection of the method utilized literature study of the relevant scientific literature as reference material. Utilization of Arduino Nano V5 in designing Programmable Logic Control by analyzing and assembling starting from input devices, process devices, and output devices. For the programming method of Programable Logic Control ladder diagrams based on Arduino Nano V5 using Outseal Studio Software. For the hardware (hardware), use the input, namely the Push Button, while for the output device, namely the magnet contractor, as a direct on line (DOL) simulation module.